WEE2 Is an Oocyte-Specific Meiosis Inhibitor in Rhesus Macaque Monkeys - Hanna, Carol B. (Society for the Study of Reproduction, Inc., 2010)
WEE1 homolog 2 (WEE2, also known as WEE1B) is a newly identified member of the WEE kinase family that is conserved from yeast to humans. The aim of the present study was to determine the spatiotemporal expression pattern and the function of WEE2 during oocyte maturation in a nonhuman primate species, the rhesus macaque. Among 11 macaque tissues examined, WEE2 transcript is predominantly expressed in the ovary and only weakly detectable in the testis. Within the ovary, WEE2 mRNA is exclusively localized in the oocyte and appears to accumulate during folliculogenesis, reaching the highest level in preovulatory follicles. Microinjection of a full-length WEE2-GFP (green fluorescent protein) fusion mRNA indicates a specific nuclear localization of WEE2 protein in both growing and fully grown germinal vesicle (GV)-intact oocytes. Taking the long double-stranded RNA-mediated RNA interference approach, we found that down-regulation of WEE2 led to meiotic resumption in a subset of GV oocytes even in the presence of a phosphodiesterase 3 inhibitor. On the other hand, overexpression of WEE2 delays the reentry of oocytes into meiosis in both mice and monkeys. These findings suggest that WEE2 is a conserved oocyte-specific meiosis inhibitor that functions downstream of cAMP in nonhuman primates.